Sales Application Design at Dorts Café Bandar Lampung - Kurniawan, Deny Firmansyah; Yansyah, Hendri (Apik Cahaya Ilmu, 2025)
Dort's Café is one of the cafés in Bandar Lampung that prioritizes a concept, taste, and service. The sales system at Dort’s Café still uses a manual system. Currently, Dort's Café does not have an online sales system for orders. Therefore, there is a need for the design of a sales application at Dort’s Café to make it easier for customers to order drinks or food at the café. The development method used in the design of this system is the Extreme Programming (XP) method. The programming language used is PHP, and the database is MYSQL. After undergoing several testing steps using BlackBox testing, it can be concluded that the program created is functioning as expected. Therefore, the research results show that with the presence of this application, Dort’s Café can make it easier for customers to order drinks and food more quickly, easily, and efficiently, as well as make it easier for admins and managers to track sales transactions, stock, and the results of sales report summaries at Dort’s Café.